Antibacterial and UV‐Blocking Bioelectronics Based on Transparent, Adhesive, and Strain‐Sensitive Multifunctional Hydrogel. Issue 7 (8th December 2021) - Sun, Xia; Yao, Mengmeng; He, Shaoshuai; Dong, Xiaoru; Liang, Lei; Yao, Fanglian; Li, Junjie
Abstract: Skin‐attachable conductive hydrogels are ideal candidates for the design of flexible and wearable electronics, and tremendous efforts are devoted to preparing multifunctional hydrogels. However, antibacterial ability and ultraviolet (UV)‐blocking property are still essential yet rarely reported. In this study, a novel ionically conductive multifunctional polyacrylamide (PAAm)/chitosan (CS)/tannic acid (TA) hydrogel (PCT hydrogel) with transparency, adhesiveness, antibacterial activity, and UV‐blocking ability simultaneously is fabricated via a facile one‐pot strategy. In the hydrogel, PAAm chains form the backbone of PCT hydrogel, CS and TA endow hydrogel with antibacterial activity (>97%) and UV‐blocking ability (>96%), respectively. More importantly, existing free ions also endue PCT hydrogel with conductivity (0.256 ± 0.005 S m −1 ) and strain sensitivity (GF > 3). The prepared PCT hydrogel‐based strain sensors can effectively monitor various human movements, indicating their huge potential in soft robotics, human–machine interaction, and health‐monitoring systems. Abstract : A novel ionically conductive polyacrylamide/chitosan/tannic acid hydrogel with transparency and adhesiveness is fabricated via a facile one‐pot strategy. The ionically conductive hydrogels with wide sensing range, high strain sensitivity, antibacterial activity, and UV‐blocking ability are further integrated as strain sensors for monitoring various human movements.